Variability and Pattern of Diseases Following Chronic Heart Failure With LV Systolic Dysfunction Who Had Elevated Serum Cardiac Troponin-1 Ievel. (KYAMC Journal, 2017)
Objective: The aim of the study was to observe age, sex, age/sex-wise distribution of diseases, occupational status, socio economic status and disease pattern involving chronic heart failure with LV dysfunction.Materials and Methods: This study was prospective, cross sectional and observational, carried out among chronic heart failure with LV systolic dysfunction patients in the department of Cardiology NICVD, Dhaka during the period of April 2004 to December 2004. In this study, total 740 patients of chronic heart failure were evaluated randomly. Among 740 patients, initially 100 patients were selected as chronic heart failure on the basis of inclusion and exclusion criteria, history, physical examination biochemical, X-ray, ECG and other relevant investigations. Finally, 60 (Sixty) patients were selected by Echocardiography who had ejection fraction 40%. Serum Cardiac Troponin-I was measured in each and every studied patients. In-hospital outcome, age distribution, sex distribution and disease pattern involving chronic heart failure with elevated serum cardiac Troponin-I level were observed in this study.Results: The mean age of the studied patients was 50-20 yrs. Highest percentage (58.33%) was in the age group 41-60 years and lowest (13.33%) in the age range 20-40 yrs. Male patients were higher in number (63.33%) than female patients (33.66%). Among the studied patients, majority were ischaemic Cardiomyopathy (43.33%) followed by idiopathic dilated Cardiomyopathy (30%), valvular heart disease (20%) and lowest (6.67%) hypertensive Cardiomyopathy. Ischaemic Cardiomyopathy were more common (23.33%) in the age group above 60 yrs. Idiopathic dilated cardiomyopathy was highest (21.67%) in age group 41-60 yrs, valvular heart diseases (15%) in the age group 41-60 yrs and equal percentage (3.33%) of hypertensive heart disease were in the age range of 41-60 yrs & above 60 yrs. Among the male patients, Ischaemic Cardiomyopathy was highest (33.33%) in number whereas idiopathic dilated cardiomyopathy was highest (13.33%) in number in female patient. In female Hypertensive heart disease was lowest in both sex. Highest number (53.33%) of patients were in poor socioeconomic status. Lowest (10%) number were rich society. In this study the most common form was left heart failure (55%) and biventricular failure was 45%. 65% patients came from rural area & 35% patients from Urban area. Sedentary worker & housewives suffer most than others.Conclusion: In this study, majority patients were male. Most of the patients were in the age group 41-60 yrs. Majority of the patients were ICM. ICM was more common above 60 yrs Lowest number of patients had hypertensive heart disease. ICM was more in male patients. IDCM was more in female patients. Chronic heart failure was more in sedentary workers than others. Rural people was more affected than Urban people. Left heart failure was more than biventricular failure. Right heart failure or EF 40% were exclude from the study.KYAMC Journal Vol. 6, No.-1, Jul 2015, Page 565-569